Phytochemical and pharmacological profiling of Balanites aegyptiaca linn.: Exploring the therapeutic potential of a traditional medicinal plant - Vikram Thakkar; Prashant Kumar Dhakad; Raghav Mishra; Ritu M Gilhotra (Phytomedicine Plus)
Numerous tree species that are underutilized can be used as food, fodder, and potentially medicinal substances. Balanites aegyptiaca (L.) Del. (B. aegyptiaca) (family Zygophyllaceae) is an evergreen xerophyte with ample beneficial attribute. It is effective to cure several diseases include malaria, epilepsy, constipation, intestinal worm infection, syphilis, asthma, jaundice, haemorrhoid, stomach aches, asthma, diarrhoea, dysentery, and wound healings. It also has contraceptive antifeedant, anti-carcinogenic, molluscicidal, antimicrobial, anti-inflammatory, anti-helminthic, antioxidant, immune-stimulant, antioxidant, antiviral and antidiabetic activities. Balanites aegyptiaca (L.) Del. (B. aegyptiaca) possesses various active compounds like lipids, carbohydrates, proteins, organic acids, alkaloids, saponins and flavonoids that mainly responsible for its pharmaceutical activities. In conclusion, the diverse pharmacological activities of this plant make it a valuable resource for developing new herbal remedies and pharmaceutical products. This review reveals bioactive compounds, medicinal uses, pharmacological significance, and toxicological effects of various parts of Balanites aegyptiaca.